Distance/Sandwich Education and E-Learning Environment in Ghana: Towards a Policy Framework - Dei, Daniel; Peprah, Williams Kwasi (Journal of Interdisciplinary Studies in Education, 2022)
In an attempt to have a citizenry comprehensibly educated to contribute significantly to the socio-economic development of the country, Ghana's Education Act 2008, 1(5-8), makes room for innovative learning: distance learning, lifelong educational programs, and open colleges. However, Ghana's higher education landscape reveals the continued dominance of the face-to-face mode of learning to the utmost neglect of other modes of innovative learning. This study shows that distance/sandwich education and e-learning environment in Ghana are stifled mainly because of high stigma, poor internet connectivity, and non-existence of national policies regulating higher learning through innovative educational programs. Through conceptual analysis, the study suggests a policy framework for enhancing higher learning through innovative modes of learning in Ghana's higher education institutions.